Application of genome tagging technology in elucidating the function of sperm-specific protein 411 (Ssp411) - Xue-Hai Zhou; Min-Min Hua; Jia-Nan Tang; Bang-Guo Wu; Xue-Mei Wang; Chang-Gen Shi; Yang Yang; Jun Wu; Bin Wu; Bao-Li Zhang; Yi-Si Sun; Tian-Cheng Zhang; et al. (Asian Journal of Andrology)
The genome tagging project (GTP) plays a pivotal role in addressing a critical gap in the understanding of protein functions. Within this framework, we successfully generated a human influenza hemagglutinin-tagged sperm-specific protein 411 (HA-tagged Ssp411) mouse model. This model is instrumental in probing the expression and function of Ssp411. Our research revealed that Ssp411 is expressed in the round spermatids, elongating spermatids, elongated spermatids, and epididymal spermatozoa. The comprehensive examination of the distribution of Ssp411 in these germ cells offers new perspectives on its involvement in spermiogenesis. Nevertheless, rigorous further inquiry is imperative to elucidate the precise mechanistic underpinnings of these functions. Ssp411 is not detectable in metaphase II (MII) oocytes, zygotes, or 2-cell stage embryos, highlighting its intricate role in early embryonic development. These findings not only advance our understanding of the role of Ssp411 in reproductive physiology but also significantly contribute to the overarching goals of the GTP, fostering groundbreaking advancements in the fields of spermiogenesis and reproductive biology.